Metaplastic Breast Carcinoma (MBC), Primary Squamous Cell Carcinoma Subtype in A 49-Year-Old Woman: A Case Report - Putu Erika Paskarani; Ni Gusti Ayu Agung Manik Yuniawaty Wetan; Ni Putu Sriwidyani; Sang Ayu Putu Yuliantini (Indonesian Journal of Cancer, 2022)
Introduction: Metaplastic Breast Carcinoma (MBC) is quite a challenging case because metaplastic breast cancer is one of the rarest subtypes of invasive breast cancer. It is reported that MBC occurs only 0.2 to 1% throughout the world. The metaplastic changes can be squamous cells or other mesenchymal cell types. Clinically, MBC presents as a large palpable mass and may be associated with rapid growth. The size of MBC tends to be larger compared with other types of invasive breast cancer ranging from 1 to more than 10 cm. Although there are several main categories of MBC, some carcinoma can be difficult to classify due to their unusual histologic patterns. This case report study is to provide a clinicopathological overview and approach to MBC.Case Presentation: We reported a 49-year-old woman who suffered from a breast mass that rapidly grew for less than one year. The microscopic findings showed squamous cell carcinoma. While molecular studies revealed triple negative results for hormone receptors although Human Epidermal Growth Factor Receptor 2 (HER2) overexpression was unusual (< 5%). Then, we confirmed with chromogen in situ hybridization (CISH) and there was no gen amplification for HER2. Microscopically, we found ductal carcinoma in situ and this finding supported breast origin.Conclusions: Metaplastic carcinoma did not have any specific and distinctive signs clinically. Metaplastic carcinoma can be monophasic (with only a metaplastic component) or biphasic with two or more components. As treatment options, our patient received conventional chemotherapy. Metaplastic breast cancer is reported to have a lower response rate to conventional adjuvant chemotherapy and worse clinical outcome after chemotherapy than other forms of triple-negative breast cancer.